PARAMETERS INFLUENCE OF INDUCTION GROOVES ON ENERGY ABSORPTION CHARACTERISTICS OF CRASH-BOX FILLED WITH FOAMED ALUMINUM - WANG ChunHua; JIANG ZongShuai; GUO Yue (Jixie qiangdu)
The foamed aluminum filled crash-box with induction grooves on the side wall was made finite element analysis in the impact process by LS-DYNA,and the parameters influence of induction grooves on the energy absorption characteristics of crash-box was studied. The results was dealt with the LS-Prepost, considering the energy absorption, peak impact force, the average impact force and energy absorption ratio, when crash-box was made two radius of 2.5 mm semicircle grooves in the upper 50% part of the side wall, in the impact process of a symmetrical stack the ideal type of shrinkage deformation, depressed peak impact force without affecting energy absorption, higher energy absorption ratio and compression efficiency wound be gotten. The finite element simulation of the impact process was feasible when the crash-box body was made the impact test by the vertical and horizontal hydraulic impact test platform.